Sintesis dan Karakterisasi Tanah Diatom Aceh sebagai Bahan Adsorben Penghasil Silika Oksida (SiO2) Tinggi - Dalsup Dalsup (Jurnal Serambi Engineering, 2022)
Diatomaceous earth is silica soil that can be produced from the weathering process of dead microorganisms that settle to the bottom of the waters and accumulate to form a sediment called diatomaceous earth. Diatomaceous earth is also a porous and silica-rich material which is thought to play a very important role in the adsorption process. The purpose of this study was to determine the presence of silica oxide (SiO2) contained in diatomaceous earth as an absorbent material for acid mine drainage. The method of this research step is to synthesize diatomaceous earth using the sol-gel method at a temperature of 50 oC at a speed of 100 rpm for 1 hour, then calcined at a temperature of 600 oC, then a characterization test is carried out to determine the composition of silica oxide compounds using SEM-EDS analysis, XRD and FT-IR. The results of the study can be observed from the results of the SEM characterization test where the high calcination temperature will affect the morphology of the smaller grain size, based on the EDS test results, the chemical composition of SiO2 is 19.37%. Based on the results of the XRD characterization test, the diffraction peak for the structure of silica oxide is at an angle of 2θ, which is 20o to 30o, while the results of the FT-IR characterization test give the presence of SiO2 which can be observed at 1800-2000 where the results are obtained at a wave number of 1867.09. These conditions provide an opportunity for diatomaceous earth to be used as an absorbent material.